Peran Dinas Pendidikan dalam Mengimplementasikan Kebijakan Pendidikan Anak Usia Dini di Kabupaten Nagan Raya - Icha Eviana; Zuhrizal Fadhly (Journal of Social and Policy Issues, 2021)
This study aims to determine the role of the Office of Education in Implementing Early Childhood Education (PAUD) in Nagan Raya Regency. Currently, early childhood education is an important education because this education is a place for the formation of a child's character or the golden age. This research method uses a qualitative method with a case study approach. The informants of this study were the Head of Early Childhood Education (PAUD) of Nagan Raya Regency, DPRK Education Commission of Nagan Raya Regency, Principal of Purwodadi Kindergarten, Manager of Family Planning (KB) Mayang Sari Gampong Purwosari, and Keuchik Gampong Pulo, Kuala Pesisir District. The results of this study indicate that the role of the Education Office in Implementing Early Childhood Education (PAUD) in Nagan Raya Regency, precisely in Kuala Pesisir Subdistrict, has not been fully maximized because the establishment of Early Childhood Education (PAUD) is still not evenly distributed throughout the Gampong in Nagan Raya Regency. In addition, there is still a lack of PAUD supervisors from the Education Office of Nagan Raya Regency, only 2 people to supervise PAUD throughout Nagan Raya Regency so that it is not fully covered and affordable. The role of gampongs in establishing PAUD is still not maximized because some gampongs still have not established PAUD even though the budget for establishing Early Childhood Education (PAUD) is already in the APBG once a year and there is still a lack of synchronization of understanding by the keuchik in the implementation of Early Childhood Education (PAUD) in the village.